The Rise of Xinjiang Studies: A JAS New Author Forum. Issue 1 (10th January 2018) - Thum, Rian; Jacobs, Justin; Cliff, Tom; Brophy, David; Kim, Kwangmin; Kobi, Madlen
Abstract : Perhaps no area of China-related scholarship has taken longer to recover from the access limitations of the mid-twentieth century than the study of Xinjiang. In the late nineteenth and early twentieth centuries, the study of Xinjiang was so fashionable that it had a wide following in the Western popular press, where the region was better known as Chinese Central Asia, Chinese Turkistan, or Eastern Turkistan. When the turmoil of the Republican and Mao eras made the region almost entirely inaccessible to outsiders, the study of Xinjiang began a long sojourn in the Western academic wilderness. After all, the earlier interest had always been tinged with Orientalist travel fantasy and imperial desires that required scholarly boots on the ground.